(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
In his paper, we have demonstrated the feasibility of a spectrally efficient wavelength-division-multiplexing-compatible optical code-division multiple-access system using 16 phase-locked laser lines within a 40-GHz tunable window as frequency and an ultrahigh frequency resolution spectral phase encoder–decoder. Coding and decoding slots using binary [0,π ] phase chips were demonstrated for four users at 5 Gb/s, and a single coded signal was separated from four copropagating signals, with bit-error rate <10 -9.